Revolutionary Brotherhood : Freemasonry and the Transformation of the American Social Order, 1730-1840 - Bullock, Steven C. (Book collections on Project MUSE., 1996)
"In the first comprehensive history of the fraternity known to outsiders primarily for its secrecy and rituals. Steven Bullocks traces Freemasonry through its first century in America. He follows the order from its origins in Britain and its introduction into North America in the 1730s to its near-destruction by a massive anti-Masonic movement almost a century later and its subsequent reconfiguration into the brotherhood we know today. With a membership that included Benjamin Franklin, George Washington, Paul Revere, and Andrew Jackson. Freemasonry is fascinating in its own right, but Bullock also places it at the center of the transformation of American society and culture from the colonial era to the rise of Jacksonian democracy." "Using lodge records, members' reminiscences and correspondence, and local and Masonic histories. Bullock links Freemasonry with the changing ideals of early American society."--Jacket